Analysis of Traffic Noise on the Sutan Soripada Mulia Road, Padang Sidimpuan City - Noni Paisah (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
Highways are infrastructure for smooth traffic, both in cities and in regions. Noise and vibration are one of the environmental health problems in large and developing cities, such as Padangsidimpuan City. The transportation sector is the main cause of environmental problems today, according to Minister of Health Regulation No.78/Men.Kes/Per/XI/1987, which is called Noise is the occurrence of unwanted sounds that disturb and/or endanger health. The noise level quality standard is used as a reference standard that ensures that a certain area/region does not cause disturbances, especially to human health and environmental comfort. (Ruly Asmarani, 2017) said that noise is a type of environmental stimulus to which each individual can respond differently. Based on the noise level captured by the SLM (Sound Level Meter), the highest noise level occurs at 07:00 - 08:00 WIB at 72.80 dB compared to other hours and is reviewed based on the characteristics of land use for the school area. The noise level limit value is 55 d.B(A) and the highest noise occurs at 07-08 am with a noise level of 72.8 decibels and the lowest noise occurs at 10-11 WIB with a noise level of 47.8 decibels. From the results of this research, it is recommended that schools close windows during the learning process to reduce the noise caused by passing vehicles.